Hubungan Diabetes Melitus Terkontrol Dan Tidak Terkontrol Dengan Faktor Risiko Obstructive Sleep Apnea (Osa) - Dharma, IGN Surya, dr. Retno Setyaningsih, Sp. PD, dr. Safari Wahyu Jatmiko (2015)
Backgrounds: Diabetes mellitus (DM) is a chronic disease that occurs when the pancreas cannot produce insulin or when there is a disruption in the body's metabolism. DM can be characterized by with a polydipsia , polyphagia, polyuria and weight loss. The weight loss is due to a decrease in muscle mass. If the muscle mass reduction occurs in nasopharynx and oropharynx, the muscle will collapse. This incident can lead to Obstructive sleep apnea ( OSA). Purpose: This research was held to answer the question is there a associated a significant diabetes mellitus patients with risk factors for OSA in Prolanis in Surakarta. Method: This research was designed using analytic observational with cross- sectional approach with samples 112 respondents. Data were analyzed by chi- square test with SPSS17.0 for windows. Results: There is a associated between DM Controlled and uncontrolled with risk OSA; p value 0,037 and Ratio Prevalens (RP) 1,524 interval confidence 95% 1,024 to 5,980. Conclusion: There is relathionship between Diabetes mellitus controled and uncontroled with risk obstructive sleep apnea.